Protective effects of MiR-146b in cerebral infarction via targeting SIRT1/FOXO1 signaling pathway: MiR-146b in cerebral infarction - Yang, Ren; Zeng, Chen (Cellular and Molecular Biology, 2023)
To observe the therapeutic effect of micro ribonucleic acid (miR)-146b on brain tissue injury in rats with cerebral infarction (CI) by regulating the Sirtuin 1 (SIRT1)/forkhead box protein O1 (FOXO1) signaling pathway, a rat model of CI was established. Lentiviral cells were used to transfect and silence or overexpress miR-146b. The rats were divided into the miR-146b inhibitor group (Inhibitors), miR-146b mimic group (Mimics) and normal group (Control). Then quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the transfection rate of miR-146b in rat brain tissues in each group. The improved method was adopted to score the nerves of rats, and the infarction volume of rats in each group was determined. Subsequently, the levels of superoxide dismutase (SOD) and reactive oxygen species (ROS) in the brain tissues in each group were measured via enzyme-linked immunosorbent assay (ELISA), the apoptosis of nerve cells in the brain tissues was detected by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), and glial fibrillary acidic protein (GFAP), S100β gene and SIRT1/FOXO1 pathway-related genes and proteins in the brain tissues were determined through qRT-PCR and Western blotting. MiR-146b exhibited a high expression in Mimics and an extremely low expression in Inhibitors. Rats in Mimics were normal in movement, and their neurological scores were close to those in Control. Rats in Inhibitors could walk normally, and their neurological scores were notably higher than those in other groups (P<0.05). In addition, Inhibitors had a remarkably larger CI volume (P<0.05), a remarkably increased ROS level and a significantly reduced SOD level compared with those in other groups. Moreover, TUNEL staining results manifested that apoptotic cells, especially glial cells, were notably increased in Inhibitors compared with those in Mimics. Besides, the messenger RNA (mRNA) expression levels of S100β and GFAP in Inhibitors were higher than those in other groups (P<0.05). SIRT1 and FOXO1 genes were increased in Mimics, which were close to those in Control. According to Western blotting results, the protein expression levels of SIRT1 and FOXO1 in Mimics were notably higher than those in Inhibitors. MiR-146b can play a protective role in CI rats by activating the SIRT1/FOXO1 signaling pathway, lowering the oxidative stress level and reducing brain tissue apoptosis.